Audio Surveillance through Known Event Classiﬁcation - Grezl, Frantisek; Cernocky, Jan (Společnost pro radioelektronické inženýrství, 2009)
The way of audio surveillance through known event classiﬁcation is presented introducing simple yet efﬁcient framework. The use of the proposed system for unknown event detection is also suggested and evaluated. Further, a speciﬁc audio event is detected with use of audio classiﬁcation, which helps the detection to focus on a signal of speciﬁc behavior. Thus it is shown that the system can be used in several applications.
Keywords: Sound classiﬁcation; event detection; audio surveillance